OH regeneration from methacrolein oxidation investigated in the atmosphere simulation chamber SAPHIR - Fuchs, H.; Acir, I. H.; Bohn, B.; Brauers, T.; Dorn, H. P.; Haseler, R.; Hofzumahaus, A.; Holland, F.; Kaminski, M.; X. Li; Lu, K.; Lutz, A.; et al. (Atmospheric Chemistry and PhysicsAtmospheric Chemistry and PhysicsAtmospheric Chemistry and Physics, 2014)
Hydroxyl radicals (OH) are the most important reagent for the oxidation of trace gases in the atmosphere. OH concentrations measured during recent field campaigns in isoprene-rich environments were unexpectedly large. A number of studies showed that unimolecular reactions of organic peroxy radicals (RO2) formed in the initial reaction step of isoprene with OH play an important role for the OH budget in the atmosphere at low mixing ratios of nitrogen monoxide (NO) of less than 100 pptv. It has also been suggested that similar reactions potentially play an important role for RO2 from other compounds. Here, we investigate the oxidation of methacrolein (MACR), one major oxidation product of isoprene, by OH in experiments in the simulation chamber SAPHIR under controlled atmospheric conditions. The experiments show that measured OH concentrations are approximately 50% larger than calculated by the Master Chemical Mechanism (MCM) for conditions of the experiments (NO mixing ratio of 90 pptv). The analysis of the OH budget reveals an OH source that is not accounted for in MCM, which is correlated with the production rate of RO2 radicals from MACR. In order to balance the measured OH destruction rate, 0.77 OH radicals (1 sigma error: +/- 0.31) need to be additionally reformed from each reaction of OH with MACR. The strong correlation of the missing OH source with the production of RO2 radicals is consistent with the concept of OH formation from unimolecular isomerization and decomposition reactions of RO2. The comparison of observations with model calculations gives a lower limit of 0.03 s(-1) for the reaction rate constant if the OH source is at-tributed to an isomerization reaction of MACR-1-OH-2-OO and MACR-2-OH-2-OO formed in the MACR + OH reaction as suggested in the literature (Crounse et al., 2012). This fast isomerization reaction would be a competitor to the reaction of this RO2 species with a minimum of 150 pptv NO. The isomerization reaction would be the dominant reaction pathway for this specific RO2 radical in forested regions, where NO mixing ratios are typically much smaller.
Keywords: ho2 concentrations; initiated oxidation; isoprene oxidation; methyl vinyl ketone; pearl river delta; radicals; rain-forest; summer 2006; tropospheric degradation; volatile organic-compounds